Uncertainty, redistribution, and the labor market since 2007 - Casey B. Mulligan (IZA Journal of Labor Policy, 2014)
Uncertainty and its composition can affect the demand for social insurance, and thereby the labor market. This paper shows that small to medium-sized increases in uncertainty or risk aversion are enough to recommend an expansion of the safety net that would be broadly similar to the actual safety net expansions in the United States since 2007, which significantly depressed the labor market. Labor market effects of uncertainty through investment and insurance channels are also examined with employer and employee labor wedges measured from 2007 through 2013.
Keywords: 330; Uncertainty; Redistribution; Taxes; Employment